Implementation of Local Knwoledge “Tri Hita Karana” on Ecotour-ISM Management in Bali - Agung SUryawan Wiranatha; Anak Agung Gde Raka Dalem (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2010)
-